An Investigation into Teachers’ Perceptions of Formative Assessment Techniques and Students’ Learning - Kausar, Fahd Naveed; Ghazala, Noreen; Jan, Shahida (Pakistan Journal of Humanities and Social Sciences, 2023)
The study's goals were to ascertain how instructors felt about formative assessment methods' impact on students' learning and how the public and private sectors differed in their views. The study also sought to determine how formative assessment methods affected university students' learning. All of the public and private universities in the Lahore district made up the population. In this investigation, the multistage sampling technique was applied. A questionnaire was used as the study's tool. Descriptive statistics was used to analyse the data. The study's conclusions showed that formative assessment methods and students' learning had a greater degree of agreement with the majority of respondents.